A Review of literature on women employment discrimination in China - Fang, Yan; Chan, Kim Ling Geraldine (Penerbit Universiti Kebangsaan Malaysia, 2024)
The transition from one-child policy to two-child policy exacerbated women's employment discrimination in China. Three-child policy may exacerbate women's employment discrimination further. This paper aims to review past literature, on women employment discrimination, causes or factors of the discrimination and the challenges the women faced. Women employment discrimination in China is also reviewed, specifically from the fertility policy perspective. A qualitative systematic thematic literature review revealed specific themes, including employment discrimination and gender discrimination, women discrimination in employment, the influence of childbearing on women employment, fertility policy, and women employment discrimination. Furthermore, there are several causes of women employment discrimination: one of them being fertility policies. The review revealed some research strengths that can strengthen new research on women employment discrimination. Gaps in terms of research limitations are identified, such as a lack of empirical data on gender bias, a paucity of data on research on gender discrimination in relation to specific fertility policies, and a lack of in-depth analyses of women's career opportunities and barriers in different cultural settings. Despite China's concern with the impact of the number of children on women employment, in-depth research on the relationship between fertility policies, especially the latest three-child policy, and women employment discrimination is limited. Therefore, there is a need to conduct more comprehensive and substantive studies on women employment discrimination that is occurring in societies, including in China, undergoing rapid social change due to accelerated modernization, capitalism, and industrialization during this Fourth Industrial Revolution (4IR).